Effect of Fertilization and Weed Management Practices on Weed Diversity and Hemp Agronomic Performance - Angeliki Kousta; Panayiota Papastylianou; Ilias Travlos; Antonios Mavroeidis; Ioanna Kakabouki (Agronomy, 2023)
The industrial hemp market is rapidly expanding, and best crop practices need to be assessed. This study aimed to determine the effect of fertilization and weed management on hemp crops and weed flora during the 2019 and 2020 growing seasons. Field experiments were laid out in a split–split plot design with three replicates: two hemp cultivars as main plots, three fertilization treatments as sub-plots, and three sub-sub-plots (weedy, weed-free, and herbicide application). For the computation of crop traits, 10 plants were randomly selected by each plot. Weed species were collected by quadrate for density and biomass weight determination. Increased fertilization rate positively affected plant height and dry biomass, while no impact was recorded on yield and yield components. The density and biomass of nitrophilous weeds were enhanced by fertilization, negatively affecting hemp growth. Marked differences were recorded on the competitive ability of cultivars since “Fedora 17” decreased the weed studied traits better than “Uso 31”. Herbicide application decreased the biomass of annual and perennial weeds by 38% and 13%, respectively, while it caused a reduction in hemp growth and yield of “Uso 31” plants. Further research should be conducted to address hemp yield losses under different cultural practices and weed control systems.